2013
DOI: 10.1038/bmt.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning followed by allogeneic transplantation in pediatric malignancies: a report from the Société Française des Cancers de l’Enfant and the Société Française de Greffe de Moelle et de Thérapie Cellulaire

Abstract: We report French prospective experience with reduced-intensity conditioning-allo-SCT in 46 patients (median age: 15.5 years, 4.8-20.2) presenting high-risk AL (n ¼ 11), Hodgkin's lymphoma (n ¼ 15) or solid tumors (n ¼ 20). Graft sources were BM (n ¼ 21), PBSC (n ¼ 20) and cord blood (CB; n ¼ 5) from related (n ¼ 20) or unrelated (n ¼ 26) donors. For CB grafts, only one patient out of five achieved sustained engraftment. For PBSC/BM grafts, engraftment rate was 95%, hematopoietic recovery times were not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…38 The median age of recipients was lower in the 2000-2010 period (8.2 years old) compared with the 1983-2009 period (11.4 years old), corresponding to broadened selection criteria related to a better understanding of the role of transplants in younger children and infants. Moreover, new conditioning regimens, such as RIC, have been recently developed for pediatric patients [39][40][41] and have enabled proposal of allo-SCT to patients with comorbidities, and also second allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…38 The median age of recipients was lower in the 2000-2010 period (8.2 years old) compared with the 1983-2009 period (11.4 years old), corresponding to broadened selection criteria related to a better understanding of the role of transplants in younger children and infants. Moreover, new conditioning regimens, such as RIC, have been recently developed for pediatric patients [39][40][41] and have enabled proposal of allo-SCT to patients with comorbidities, and also second allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced‐intensity conditioning (RIC) regimens have shown favourable outcome in adults with AML but there have been very limited experiences in children. A French series included eight AML children considered ineligible for myeloablative transplantation due to severe infection or previous myeloablative therapy and found a 3‐year event‐free‐survival of 75% (Paillard et al , ). A recent international study comparing RIC ( n = 39) with matched cases receiving myeloablative regiments ( n = 141) found similar rates of toxicity, relapse and survival (5‐year OS 45% vs. 48%) (Bitan et al , ).…”
Section: Type Of Hsctmentioning
confidence: 99%
“…NMAC/RIC have been reported as the preparative regimen for allo-HSCT of pediatric patients with hematological malignancy in poor PS and for second allo-HSCT192021222324. In these days, non TBI-based RTMAC regimens have been used for first allo-HSCT of pediatric patients with hematological malignancy252627.…”
Section: Discussionmentioning
confidence: 99%
“…Graft failure is one of the major problems for CBT after an NMAC/RIC/RTMAC regimen202126. Paillard et al 20 and Bradley et al 21 reported that 4 of 5 CB and 6 of 21 CB, respectively, failed to engraft into pediatric patients, when RIC was used as the preparative conditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation